Beginning Adobe AIR - Tretola, Rich (Wiley pub., 2008)
If you're ready to take advantage of Adobe Integrated Runtime (AIR) to build desktop-based Rich Internet Applications, then this is the book for you. After introducing you to AIR, Adobe expert Rich Tretola discusses the different programming languages and tools you can use for development. He presents multiple methods for storing data, including within the file system and embedded database as well as storage on remote servers. This guide is a perfect mix of tutorials and hands-on coding, and provides the resources you need to build AIR applications quickly